A Comparison of Problems Faced by Mathematics Teacher - Educators in Developing and Developed Countries - A Case Study of Nepal and England - Koirala, Hari Prasad (Tribhuvan University Journal, 2010)
There is still a shortage of qualified mathematics teachers in schools in developed and developing countries. It may be because of the problems facing mathematics teachers in schools and the problems facing mathematics teacher-educators in colleges of education who are responsible in producing qualified mathematics teachers. Mathematics teachers and educators are more concerned about the former and the latter is usually neglected. This article tries to trace out the problems facing mathematics teacher-educators in both developing and developed countries on the basis of a study carried out in Nepal and a similar study in England. 15 out of 16 and 135 out of 247 mathematical educators in Nepal and England respectively took part in these studies. It was found that lack of books and journals, teaching facilities and aids and negligible grants for research or personal studies are the main problems for mathematics teacher-educators both in Nepal and England. However it was seen that the problems faced by mathematical educators in Nepal were more serious than those of England. Key words: Mathematics teacher; Developing and Developed countries; Nepal and England Tribhuvan University Journal Volume XIV, 1991 Page: 15-25 Uploaded date: 5 October, 2010